EPILEPSY IN 11 PATIENTS WITH TYPICAL RETT SYNDROME CAUSED BY MECP2 MUTATION: CLINICAL AND ELECTROENCEPHALOGRAPHIC CHARACTERISTICS, COURSE, THERAPY (RESULTS OF THE AUTHORS’ OBSERVATIONS) - M. Yu. Bobylova; K. Yu. Mukhin; I. V. Ivanova; I. V. Nekrasova; O. A. Pylaeva; N. Yu. Borovikova; E. S. Il’ina (Русский журнал детской неврологии, 2016)
Examinations were made in 11 female patients aged 3 to 23 years with Rett syndrome and typical mutation in the MECP2 gene, who had been followed up from 2006 to 2015. The investigators evaluated neurological and psychic status (systematically) and performed continuous video electroencephalographic (EEG) monitoring (if clinically indicated), magnetic resonance imaging, and molecular cytogenetic examination. Epilepsy was diagnosed in 6 (54.5 %) patients: symptomatic focal epilepsy in 5 cases and symptomatic generalized epilepsy in 1. The mean age at epilepsy onset was 3 years and 9 months. Generalized epileptic seizures were noted in 60 % of cases and focal ones in 40 %. EEG changes were revealed in 9 patients, 5 with slowing of background activity, 2 with regional epileptiform activity, and 1 with diffuse epileptiform activity that corresponded to that of the benign epileptiform patterns of childhood. Five patients were recorded to have multiregional epileptiform activity.